Network configuration as a measure of power in global production networks - Panagiotis Iliopoulos; Giorgos Galanis; Ashok Kumar; Lilit Popoyan (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2020)
Power is one of the key components in understanding and analyzing global production and is central to the analytical frameworks of both GVCs and GPNs. By focusing on firms' power within GPNs, we are able to draw a novel analytical link between the governance structures of GVCs and network configuration presented in recent versions of GPNs. Using global input-output data, we show that the network structure of global production helps determine the distribution of power among firms in different economic sectors and, consequently, it influences the governance structures of supply networks. More specifically, we find a very high correlation between the distribution of profits and a sector's position in global production, captured by its (total strength) centrality. Based on this, we are able to provide a quantitative measure of power within global production and its governance structures.
Keywords: C67; D57; D85; L11; 330; Global production networks; global value chains; power relations; network theory